Carbon capture utilization and storage promotes poverty alleviation and sustainable development in China - Zhengguang Liu; Yuntian Chen; Xuemei Wei; Congyu Zhao; Yangkai Zhang; Haizhi Luo; Kangyin Dong; Zhenhua Rui; Hao Xu; Lei Yang; Jinyue Yan; Fengqi You; et al. (Communications Earth & Environment)
Abstract Integrating of carbon capture, utilization, and storage with poverty alleviation strategies presents an innovative and sustainable development paradigm. Regional poverty, often exacerbated by challenging geographical conditions, can be transformed into opportunities for carbon storage development, promoting energy and economic rebalancing while avoiding poverty and resource traps. By introducing an evaluation index grounded in Sustainable Development Goals and technical requirements, we achieve a harmonious balance between potential and economic development. Techno-economic analysis in coal plant renovation and oil field projects demonstrates this project triggers a 7.70% growth in local gross domestic product per capita, and a decrease of 4.85% in local carbon dioxide emissions. Construction costs in impoverished regions can be over 20% lower than in more affluent areas for projects of the same scale because of cheaper labor and lower transportation and storage costs, highlighting the cost-effectiveness of pursuing poverty alleviation through carbon capture, utilization, and storage in China. This paper also emphasized the carbon storage demand in future’s energy transition of China. The status of policy implementation underscored the significant potential of carbon capture, utilization, and storage in contributing to poverty alleviation in the world’s largest carbon emitter and developing country, potentially serving as a critical testbed globally.